How information processing and risk/benefit perception affect COVID-19 vaccination intention of users in online health communities - Hao Liu; Liyue Gong; Cao Wang; Yunyun Gao; Yi Guo; Minhan Yi; Hao Jiang; Xusheng Wu; Dehua Hu (Frontiers Media S.A., 2023)
ObjectiveTo investigate the relationship among information processing, risk/benefit perception and the COVID-19 vaccination intention of OHCs users with the heuristic-systematic model (HSM).MethodsThis study conducted a cross-sectional questionnaire via an online survey among Chinese adults. A structural equation model (SEM) was used to examine the research hypotheses.ResultsSystematic information processing positively influenced benefit perception, and heuristic information processing positively influenced risk perception. Benefit perception had a significant positive effect on users' vaccination intention. Risk perception had a negative impact on vaccination intention. Findings revealed that differences in information processing methods affect users' perceptions of risk and benefit, which decide their vaccination intention.ConclusionOnline health communities can provide more systematic cues and users should process information systematically to increase their perceived benefits, consequently increase their willingness to receive COVID-19 vaccine.